Base pressure control and temperature distribution along the duct at supersonic Mach number: a comprehensive CFD approach - Part 1 - Jais, Amirullah; Khan, Ambareen; Akhtar, Mohammad Nishat; Khan, Sher Afghan (Pushpa Publishing House, India, 2025)
Sudden expansion is widespread in industry and at the base of rockets and missiles. Managing base pressure in supersonic flows is crucial for reducing drag and enhancing the performance of high-speed vehicles, such as missiles and rockets. This study investigates the use of quarter-circular ribs to regulate base pressure as a passive control method. Computational simulations investigate how the rib radius and placement near a backward-facing step influences flow behavior, including recirculation and vortex formation. In the study, the inertia parameters considered were a Mach number of M = 1.7 and the nozzle pressure ratio (NPR) in the range of 3 to 11. The geometrical parameters considered were the area ratio A2/A1 = 4, the cross-sectional area of the duct-to-nozzle exit, and the length-to-diameter L/D ratio, ranging from 1 to 6. The quarter-circle radii considered were 1.5 mm, 2 mm, and 3 mm, and the ribs were located at L/D = 0.5, 1, 1.5, and 2. The goal is to identify the optimal rib geometry and location that maximizes aerodynamic efficiency. The results show that the optimum rib radius and locations are 3 mm and L/D = 2. The rib radius of 1.5 mm does not show any definite pattern. In contrast, the 3 mm rib radius exhibits a progressive increase in the base at various locations within the duct. This study includes the results for the rib facing the curved part of the rib only. Hence, a 3 mm rib radius seems to be the best option if the application is to reduce the base drag to a considerable level.